The first record of Hemiorchis pantlingii King (Zingiberaceae) in the flora of Bhutan - Gyeltshen, Phub; Tashi, Chogyal (Biodiversity: Research and Conservation, 2025)
A botanical exploration carried out in Samtse District (south-western Bhutan) in 2019 led to a discovery of the rare perennial herb Hemiorchis pantlingii. It was found in shaded areas within a subtropical plantation forest of Shorea robusta Gaertn. at an elevation of 386 m. This species differs from H. rhodorrhachis in lateral staminodes, with apex ± truncate, yellow to orange-yellow, but also labellum mid-region distinctly raised with a single broad keel, and apical projection – a single blunt lobe. The plant is assessed as near threatened (NT) under the IUCN Red List categories and criteria.